Impact of community care services on the health of older adults: evidence from China - Ma, Wenjing; Shen, Zheng (Frontiers in Public Health, 2023)
Introduction The rapid growth in the population of older adults has put tremendous pressure on medical and social services in countries including China. Community care services are a feasible solution for promoting healthy aging in developing countries. This study investigated the association between community care services and the health of older adults in China. Method Using nationally representative survey data from China, consisting of four waves conducted in 2005, 2008, 2011, and 2014, a balanced panel dataset was constructed using a sample of 4,700 older adults (33.1% aged 80 years or older, 51.0% residing in rural areas, and 48.8% women). We employed linear regression models with time-fixed effects and instrumental variable approaches to estimate the effect of community care services on the health of older adults, as well as the differences in these effects across subgroups. Results The results showed that community care services lead to a significant improvement in both the objective and subjective health and wellbeing of older adults. Among the various service offerings, spiritual recreation services led to a significant increase in both objective and subjective health scores, while medical care services significantly improved wellbeing. This suggests a varied effect of subdivided service types. Further evidence suggests that spiritual recreation services have a significant health-enhancing effect on multiple groups of older adults, and the effect of medical care services is more effective for those living in rural areas, women, and those who are older than 80 years (all p < 0.05). Discussion Few studies have examined the impact of community care services on the health of older adults in developing countries. The findings present important implications for improving the health status of older adults and provide suggestions for establishing a socialized aged care system in China.